Answer:
-3x+10y
Step-by-step explanation:
Given the expression [tex]-4\left(2x-y\right)+y+5\left(x+y\right)[/tex], we are to simplify by combining the like terms. On simplification we have;
[tex]= -4\left(2x-y\right)+y+5\left(x+y\right)[/tex]
Open the parenthesis:
[tex]= -4(2x)-4(-y)+y+5(x)+5(y)\\\\= -8x+4y+y+5x+5y[/tex]
Collect the like terms:
[tex]= -8x+5x+4y+y+5y[/tex]
Sum up the resulting expression
[tex]= -8x+5x+4y+y+5y\\= -3x+10y[/tex]
Hence the required expression on simplification is -3x+10y